Live agent training as an important process safety measure to strengthen resilience in hazardous (CBRN) work situations - Stolar, Alexander; Friedl, Anton (Journal of Emergency Management, 2024)
Various occupational groups as well as emergency responders are important human factors in combating incidents and emergencies in a broad range. Negative deviations from a process-safe condition should be detected and transformed into a safer condition to prevent negative consequences. Therefore, training and education of personnel is an important measure in this case as well as a major influencing factor on the vulnerability to errors during operations and their resilience. From lack of training to incorrect execution due to excessive stress, fear, or unfamiliar situations, it is important to counteract this with targeted training under conditions that are as close to reality as reasonably achievable. Realistic training situations involving live agents allow to recognize mistakes or inadequacies not only in personnel but also in material or in mission planning and to create a more effective working environment. Many violations of work guidelines are due to well-intentioned deviations from nonexecutable standard operation procedures that have never been tested. Repeated, progressive training under real hazardous conditions can help to strengthen mission readiness and resilience of teams. It better prepares them for their dangerous activities.